Access to a Library of 1,3-disubstituted-1,2,3-triazenes and Evaluation of their Antimicrobial Properties - Seck, Insa; Ndoye, Samba F.; Ba, Lalla A.; Fall, Alioune; Diop, Abdoulaye; Ciss, Ismaïla; Ba, Abda; Sall, Cheikh; Diop, Amadou; Boye, Cheikh S.; Gomez, Generosa; Fall, Yagamare; et al. (Current Topics in Medicinal Chemistry, 2020)
Background: Due to the rapid development of microbial resistance, finding new molecules became urgent to counteract this problem. Objective: The objective of this work is to access 1,2,3-triazene-1,3-disubstituted, a class of molecule with high therapeutic potential. Methods: Here we describe the access to 17 new triazene including six with an imidazole-1,2,3-triazene moiety and eleven with an alkyl-1,2,3-triazene moiety and their evaluation against five strains: two gram (-): Escherichia coli ATCC 25921 and Pseudomonas aeruginosa ATCC 27253; two gram (+) : Staphylococcus aureus ATCC 38213 and Enterococcus faecalis ATCC 29212; and one fungi: Candida albicans ATCC 24433. Results: All strains were sensitive and the best MIC, 0.28 μM, is observed for 4c against Escherichia coli ATCC 25921. Compound 9, 3-isopropynyltriazene, appears to be the most interesting since it is active on the five evaluated strains with satisfactory MIC 0.32 μM against Escherichia coli and Pseudomonas aeruginosa and 0.64 μM against Enterococcus faecalis and Pseudomonas aeruginosa. Conclusion: Comparing the structure activity relationship, electron withdrawing groups appear to increase antimicrobial activity.
Keywords: Resistance